Automated refraction after trifocal and trifocal toric intraocular lens implantation. Issue 3 (May 2021) - Rementería-Capelo, Laureano A; García-Pérez, Jorge L; Contreras, Inés; Blázquez, Vanesa; Ruiz-Alcocer, Javier
Background: To analyze the correlation between automated refraction and manifest refraction after implantation of a trifocal intraocular lens or its toric version. Methods: This cross-sectional study involved 105 eyes of 105 patients. Subjects were divided in two groups: 62 with trifocal (AcrySof PanOptix) and 43 with trifocal toric (AcrySof PanOptix Toric) intraocular lenses. Automated refraction was employed as starting point for obtaining the manifest refraction. Automated refraction and manifest refraction measurements were analyzed and compared using the vector analysis 3 months after the surgery. Results: In both groups, the higher differences between automated refraction and manifest refraction measurements were found for the cylinder and the spherical equivalent (M). Cylinder values for PanOptix were: −0.60 ± 0.36 D with automated refraction and −0.17 ± 38 D with manifest refraction ( p < 0.001); for PanOptix Toric, the values were: −0.49 ± 0.31 D with automated refraction and −0.05 ± 0.21 D with manifest refraction ( p < 0.001). M values for PanOptix were: −0.23 ± 0.31 D with automated refraction and −0.03 ± 0.16 D with manifest refraction ( p < 0.001); for PanOptix Toric, the values were: −0.13 ± 0.40 D with automated refraction and 0.01 ± 0.12 D with manifest refraction ( p < 0.001). For the PanOptix group, intraclass correlation coefficients were: 0.51 (sphere), 0.64 (cylinder), 0.42 (M), 0.62 (J0), and 0.37 (J45). For the PanOptix Toric group, the intraclass correlation coefficients were: 0.39 (sphere), 0.61 (cylinder), 0.39 (M), 0.53 (J0), and 0.09 (J45). Conclusion: The results of this study suggest that patients implanted with the trifocal and the trifocal toric intraocular lens under study showed similar automated refraction results between them, with a slight trend to more negative amounts of cylinder and M. Nevertheless, clinicians should carefully confirm all parameters of the refraction with manifest refraction.